Uso alimentar de animais silvestres por estudantes de terras indígenas da Paraíba - Santos, Claudileide Pereira dos (2019)
Game animals and fishery resources make up the diet of many communities, often representing the only protein source available. Knowing the factors related to this consumption becomes important in the formulation of sustainability practices and environmental management. The present study aimed to record and analyze the factors related to the consumption of wild meat by students living in Potiguara lands, in the north coast of Paraíba. For this, questionnaires were applied to 843 students in schools distributed in the indigenous lands of the region. We hypothesize that consumption and preference for meat of domestic animals is higher than meat of wild animals and that consumption of game animals and fishing resources is related to the type of occupation of parents and location of villages. To test these hypotheses An to use the following analyzes:Chi-square test, Mann-Whitney test, generalized linear models and ranking analysis. Our results showed that meat consumption and preference for domestic animals are higher than for wild animals. However, bushmeat is an important food resource for students and their families and is related to the occupation of the students' parents and the location of the villages. In this way, wild animals play an important role for this people and possibly the presence of an environmental protection area is essential for the maintenance of the biodiversity used by this people.